Examination of marital adjustment and sexuality in patients with schizophrenia - Fetelizade, Sebnem; Eker, Salih Saygın (The European Research Journal, 2020)
Objectives: The main aim of the study is to compare marital adjustment and sexuality in schizophrenia patients.Methods: The sample of the study consists of 48 outpatients with a diagnosis of schizophrenia according to DSM V by the Department of Psychiatry, Bursa Uludağ University School of Medicine and 48 healthy volunteers. Sociodemographic Information Form, Marriage Adjustment Scale (MAS), Arizona Sexual Experiences Scale (ASEX) - (Female and Male form) are applied to both groups.Results: A significant difference was observed between individuals with schizophrenia and healthy group according to sexual dysfunction. The incidence of sexual dysfunction in schizophrenia patients is high. While the average values of the individuals' MAS were higher in the healthy group, no significant difference was found between the groups according to the MAS total score. Conclusions: There is no difference in terms of compliance with marriage between the healthy group and schizophrenic patients, but there is a difference in terms of sexual function. Data from this study suggest that schizophrenia may not be a factor in marital adjustment but may be a factor that may cause sexual dysfunction. All schizophrenic patients in our study used drugs. It cannot be ruled out that drug use may cause sexual dysfunction.